Efektivitas Pelaksanaan Kurikulum untuk Meningkatkan Kualitas Pendidikan di TK Dewantara Titi Kuning Kecamatan Medan Johor - Windy Zulianda; Indra Muda; Bahrum Jamil (Universitas Medan Area, 2020)
Early childhood education is directed to facilitate the child's healthy growth and optimal development in accordance with the values, norms, and expectations of the community. The aim is to form quality children, ie children who grow and develop according to their level of development. This research is in the form of descriptive qualitative approach that is describing the data obtained from the field and explain it in words. This study aims to determine the role of Dewantara Kindergarten in improving the quality of early childhood education in Titi Kuning Village, Medan Johor District. Based on the data that has been collected can be seen from several factors, namely, norms, concepts, and individual behavior that has been used to see how the role performed by Dewantara Kindergarten. all factors went well, So with the role of kindergarten Dewantara, Titi Kuning Village, Medan Johor District, it can improve the quality of early childhood education.